C2: a new overlay network based on CAN and Chord. (3rd January 2006) - Cai, Wenyuan; Zhou, Shuigeng; Qian, Weining; Xu, Linhao; Tan, Kian-Lee; Zhou, Aoying
In this paper, we present C 2, a new overlay network based on CAN and Chord. It is primarily designed for a dynamic environment in which peers join and depart the network frequently. For an n-peers C 2 system, each peer maintains only about O(log n) of other peers' information, and achieves routing within O(log n) hops. For each peer's joining or departure, C can, in high probability, update the routing tables with no more than O(log n) messages. What distinguishes C 2 from many other peer-to-peer data sharing systems is its low computation cost and its high routing efficiency in a dynamic network. Even in the case that a considerable number of peers fail simultaneously, i.e., several other peers' routing tables are out of date, the average number of hops for successful routing remains acceptable.